2017
DOI: 10.1038/ng.3893
|View full text |Cite
|
Sign up to set email alerts
|

Identification of liver-specific enhancer–promoter activity in the 3′ untranslated region of the wild-type AAV2 genome

Abstract: Vectors based on adeno-associated virus type 2 (AAV2) are powerful tools for gene transfer and genome editing applications. The level of interest in this system has recently surged in response to reports of therapeutic efficacy in human clinical trials, most notably for those in patients with hemophilia B (ref. 3). Understandably, a recent report drawing an association between AAV2 integration events and human hepatocellular carcinoma (HCC) has generated controversy about the causal or incidental nature of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 58 publications
3
73
0
Order By: Relevance
“…The observation that the internal transgene promoter was not necessary for the increase in tumor incidence is corroborated with a more recent study that noticed the same effect when even only a portion of the viral ITR was integrated [80]. The fact that a region of some rAAV2 ITRs contains a bidirectional binding site for a strong liver-specific transcription factor (HNF1α) aids the speculation that unforeseen integration of AAV ITRs can influence the expression of neighboring genes, similar to the situation observed following retroviral integration [72,81]. It is important to acknowledge, however, that larger animal models have not presented with rAAV-associated HCC and that so far no similar cancers have been reported in the numerous rAAV liver gene therapy clinical trials that have been undertaken [82,83].…”
Section: A Brief History Of In-vivo Gene Therapysupporting
confidence: 58%
See 1 more Smart Citation
“…The observation that the internal transgene promoter was not necessary for the increase in tumor incidence is corroborated with a more recent study that noticed the same effect when even only a portion of the viral ITR was integrated [80]. The fact that a region of some rAAV2 ITRs contains a bidirectional binding site for a strong liver-specific transcription factor (HNF1α) aids the speculation that unforeseen integration of AAV ITRs can influence the expression of neighboring genes, similar to the situation observed following retroviral integration [72,81]. It is important to acknowledge, however, that larger animal models have not presented with rAAV-associated HCC and that so far no similar cancers have been reported in the numerous rAAV liver gene therapy clinical trials that have been undertaken [82,83].…”
Section: A Brief History Of In-vivo Gene Therapysupporting
confidence: 58%
“…Exploiting this knowledge, researchers have used in-silico analysis methods to derive synthetic promoters that are both strong and liver specific [71]. Interestingly, analysis of the ITR region of the AAV2 genome (often used as the genome for many different AAV pseudotypes) has revealed that it contains transcription factor binding sites for, among others, hepatocyte nuclear factor 1 homeobox A (HNF1α) [72]. This transcription factor is strongly liver-specific and, while possibly beneficial or at least neutral in liver-directed gene therapy, could conceivably be detrimental when using an AAV2 genome to target a different tissue or organ, by prompting off-target expression in the liver.…”
Section: A Brief History Of In-vivo Gene Therapymentioning
confidence: 99%
“…[116][117][118][119][120][121][122][123] It is particularly encouraging that preclinical studies in haemophilia mice, dogs or nonhuman primates did not reveal any increased tumorigenic risk after AAV gene transfer. [116][117][118][119][120][121][122][123] It is particularly encouraging that preclinical studies in haemophilia mice, dogs or nonhuman primates did not reveal any increased tumorigenic risk after AAV gene transfer.…”
Section: Con Clus I On S and Per S Pec Tive Smentioning
confidence: 99%
“…123 Nevertheless, efficient site-specific integrating vectors based on designer zinc finger nucleases, CRISPR/Cas9 or nuclease-free targeting approaches into "safe harbour" loci could potentially minimize this risk. 123 Nevertheless, efficient site-specific integrating vectors based on designer zinc finger nucleases, CRISPR/Cas9 or nuclease-free targeting approaches into "safe harbour" loci could potentially minimize this risk.…”
Section: Con Clus I On S and Per S Pec Tive Smentioning
confidence: 99%
“…Wild-type AAV has been implicated in hepatocellular carcinoma, although both this result and the relevance to gutless vectorized AAV has TA B L E 1 The knowns and unknowns of gene transfer Known knowns Haemophilia gene transfer is curative through at least 2 years Variable transgene expression intra-and inter-individual Short-term, self-limited hepatocyte toxicity occurs frequently via 3 independent potential mechanisms Pre-existing immunity can abrogate transduction Known unknowns Degree and consequences of integration into genome Risk of insertional oncogenesis Aetiologies of types of hepatocyte toxicity Effect of heterogeneous spatial transduction within liver from portal triads to central veins Effect of ubiquitous distribution of vector throughout body Leakiness of promoters Kinetics of viral uncoating and assembly of stable AAV-derived episomes within nucleiVariability in protein production between cells within and between hostsInfluence of AAV packaging size limitations on gene expressionHow to circumvent pre-existing immunity to prior AAV infection How can readministration of the transgene be achievedIs transgene immune response or transgene tolerance dominatingLong-term persistence of transgene in growing liversUnique features of previously HCV-infected liversCan robust manufacturing be scaled up for commercializationUnknown knownsUnexpected events recognized as anticipated in hindsight such as exaggerated toxicityClinical liver toxicityUnknown unknownsUnexpected outcomes based on inadequately understood known unknownsLoss of gene expression AAV, adeno-associated virus; HCV, hepatitis C virus F I G U R E 1 Pierce and Iorio [Colour figure can be viewed at wileyonlinelibrary.com] reviewed in38 ). A recent report found an enhancerpromoter activity in the 3′ untranslated region of AAV2 that may exist in some vectorized AAVs, since most utilize pseudotyping of portions of AAV2 from the end of the capsid gene to the 3′ internal terminal repeat 39.…”
mentioning
confidence: 99%